(untitled) (The Research of Medical Science Review, 2025)
Objective: To compare the duration of labor in nulliparous women receiving dates with those not receiving dates in late pregnancy. Study Design: Randomized controlled trial. Study Setting: Obstetrics and Gynecology Department, Ali Fatima Hospital, Lahore. Study Duration: Six months (from June to Nov, 2024) Methodology: A total of 80 nulliparous women aged 18–35 years with singleton, cephalic pregnancies at 37–38 weeks gestation were included. Participants were randomly assigned into two groups: Group A (intervention, n=40) received 70–75 grams of date fruit three times a week from the 37th week, while Group B (control, n=40) received standard antenatal care without dates. Randomization was done using a random number table. All participants were monitored for onset of labor. If labor had not commenced by 41 weeks, induction was performed. Duration of the active, second, and third stages of labor, along with type and mode of delivery, were recorded. Data were analyzed using SPSS version 26.0. Independent t-tests compared labor durations, and chi-square tests were used for categorical variables. A p-value ≤0.05 was considered statistically significant. Results: The intervention group experienced a higher rate of spontaneous labor and normal vaginal delivery. The active and second stages of labor were significantly shorter in the date group compared to the control. No significant difference was observed in the third stage duration. Conclusion: Date consumption in late pregnancy significantly reduces labor duration and promotes spontaneous vaginal delivery. It may serve as a safe, culturally acceptable dietary approach to support natural childbirth in nulliparous women